Avaliação do processo de nanofiltração integrado ao biorreator com membranas inoculado com leveduras para tratamento de lixiviado de aterro sanitário - Natália Cristina de Melo Silva (2017)
Landfill leachates have complex chemical and microbiological characteristics and are composed of substances of difficult degradation. The integration of membrane separation technology into biological treatments represents an alternative to conventional treatments for this effluent. The nanofiltration appears as a polishing step, allowing the effluent treated for reuse in the own landfill or discharged into watercourses, in compliance with the legal standards required for disposal. In this context, the performance of the nanofiltration process of a leachate sample from a sanitary landfill of Minas Gerais (Brazil) that had previously been treated in a membrane bioreactor, inoculated with Saccharomyces cerevisiae, preceded by an air stripping of ammoniacal nitrogen was evaluated. The influences of concentration polarization and fouling phenomena on the permeate flux decline at different operating pressures was analyzed. The highest reduction of the permeate flow was obtained for the higher operating pressure, 12 bar, being this attributed mainly to the concentration polarization. The membrane fouling mechanisms were investigated using resistance-in-series and the Hermia models. The main resistance to permeation was attributed to reversible phenomena and to the membrane own hydrodynamic resistance, which was responsible for more than 60% of the total resistance at 10 bar. The adjustment of the experimental data to the Hermia models revealed that cake formation was the mechanism that best explained the membrane fouling at pressures of 8, 10 and 12 bar, but not it was not the only one. Intermediate, complete, and standard pore blocking were also checked. Permeate recovery rate of 40% was obtained for the process of nanofiltration at 10 bar, with a permeate flux 52% lower than the initial one. At 10 bar removal percentages of pollutants by the membrane were more significant: 96% chemical oxygen demand, 98% total organic carbon, 90% for sulphate, and greater than 70% for monovalent ions (chloride and potassium). High rejection of pollutants was obtained with integrated MBR-NF system leading the treated effluent able to be reused in the own landfill or discharged into watercourses in accordance with standards limits for disposal